2017
DOI: 10.1186/s12886-017-0560-x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular knowledge and practice among type 2 diabetic patients in a tertiary care hospital in Bangladesh

Abstract: Background and aimsDiabetes mellitus is likely to have a major effect on vision, and adequate knowledge of its ocular manifestations is of substantial importance to diabetic patients. The study aimed to assess the ocular knowledge and practices among Type 2 diabetic patients of Bangladesh.MethodsThis cross-sectional study included 122 diabetic patients from the outpatient department (OPD) of the apex diabetic healthcare hospital of the country under the sponsorship of the Diabetic Association of Bangladesh (BI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
16
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 21 publications
(20 reference statements)
11
16
8
Order By: Relevance
“…This study also showed that 39.6% [34.3-45.7%] of participants had good eye checkup practice regarding diabetic retinopathy and 60.4% of participants had poor eye checkup practice regarding DR. This finding is in line with the study done in South Africa (25)and Bangladesh (17)where the practice of eye examination was reported as 37% in both studies. On the other hand, the result from the present study is lower than the result obtained from Australia (27) The reasons for not getting eye examination were lack of visual symptoms in 56.7% participants and followed by 32.1% who felt they needed to be referred by their physician before getting their eyes examined.…”
Section: Factors Associated With Eye Check-up Practice Of Diabetic Resupporting
confidence: 91%
See 1 more Smart Citation
“…This study also showed that 39.6% [34.3-45.7%] of participants had good eye checkup practice regarding diabetic retinopathy and 60.4% of participants had poor eye checkup practice regarding DR. This finding is in line with the study done in South Africa (25)and Bangladesh (17)where the practice of eye examination was reported as 37% in both studies. On the other hand, the result from the present study is lower than the result obtained from Australia (27) The reasons for not getting eye examination were lack of visual symptoms in 56.7% participants and followed by 32.1% who felt they needed to be referred by their physician before getting their eyes examined.…”
Section: Factors Associated With Eye Check-up Practice Of Diabetic Resupporting
confidence: 91%
“…The odds of good eye checkup practice among participants who had good knowledge of DR was 17 times (AOR=17.5, CI: 5.97-51.3) more as compared to those who had poor knowledge. (Table 6) However, the result in this study is lower than the studies conducted in Bangladesh (17) and Saudi Arabia(22) which were 76% and 64% respectively. This difference might be due to lack of organized diabetic education facilities, less participation of media and non-governmental organizations in awareness creation about diabetic retinopathy in present study setting.…”
Section: Factors Associated With Eye Check-up Practice Of Diabetic Recontrasting
confidence: 82%
“…Eye diseases caused by diabetes include DR, cataract and macular degeneration (Geloneck et al, 2015). The longer the duration of diabetes, the more complications occur, and the higher the risk of visual impairment or even blindness (Ahmed et al, 2017).…”
Section: Diabetic Ocular Complicationsmentioning
confidence: 99%
“…Knowledge: Respondents who scored greater than or equal to the mean (≥5.55) of knowledge questions were considered to have good knowledge and those who scored below the mean were considered as having poor knowledge (5,17).…”
Section: Operational De Nitionsmentioning
confidence: 99%